Der erniedrigte Christus = Самоуничижение Христа Metaphern und Metonymien in der russischen Kultur und Literatur = Метафоры и метонимии в русской культуре и литературеТом 2: Русские репрезентации и практики - Uffelmann, Dirk (Academic Studies Press, 2024)
This three-volume book investigates the Russian transformations of one of the central concepts of Greek Christology, the self-humiliation or kenosis of Christ. The author applies rhetoric (paradox, metaphor, metonymy) as a means to elucidate mechanisms of theological persuasion and to trace the representations of the humiliated Christ and his imitations in various media from liturgy and iconology to everyday practice and literary fiction. The exploration of post-Christian literature of the 19th and 20th century (N. Chernyshevskii, M. Gor'kii, N. Ostrovskii, Ven. Erofeev, Vl. Sorokin) demonstrates the existence of a kenotic Christology after Christianity.